Drug Induced Gingival Overgrowth In Elderly Stroke : A Case Report - Pinzon, Rizaldy Taslim; Nathanael, Hanshel Everad (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: Drug-induced gingival overgrowth has been reported as adverse effect of certain medication, including amlodipine, in susceptible individuals. The exact mechanism of gingival hypertrophy remains unclear and may be related with multifactorial factors. Gingival hypertrophy related with speech and mastication problem, poor oral hygiene and aesthetic appearance. Case Presentation: We report the case of a 64-year-old male with post stroke and hypertension who developed gum hypertrophy following amlodipine use for 3 years. Maintenance of oral hygiene and substitution of offending medication was performed as the first step in management. Conclusion: A case of DIGO associated with amlodipine on post stroke patient with hypertension that causing difficulties in mastication and diffuse gingival enlargement. After the amlodipine was substituted with candesartan and oral hygiene was performed, leading to significant alleviation of the symptoms Keywords: Gingival hypertrophy; Amlodipin; DIGO; Adverse event